the phenomenon of self-fragmentation in the poetry of Abu Muzaffar Al-Abiord - Dheyab Sarhan Sallo, Dr. (lark, 2026)
This research addresses the phenomenon of self-fragmentation in the poetry of Abu Muzaffar Al-Abiordi. It explores how the poet expresses the intertwining and conflict of emotions and thoughts within the human soul through delicate and symbolic poetic imagery. Selected texts were analyzed to demonstrate how Al-Abiordi reflects a state of internal disintegration, between love and pain, hope and despair, and awareness of reality and fantasy. The study also shows that poetry articulates the deep psychological struggle experienced by individuals in various situations, and that self-fragmentation is one of the most prominent aspects of the human experience addressed by the poet in a distinctive artistic style. This style reflects the depth of psychological pain and longing, revealing facets of division and hesitation within the self
Keywords: Fragmentation, Self, Abbasid Poetry, Al-Abiordi.